The role of leaders' emotions management towards leadership effectiveness in non-government organizations - Nisar, Qasim Ali (2019)
Non-government organizations are challenged with ineffective leadership due to leaders’ inappropriate management of emotions that lead towards unfavorable followers’ attitudes and behaviors. Therefore, this study is undertaken to examine the role of leaders’ emotions management towards leadership effectiveness. It aims to investigate the effect of leaders’ emotional labor strategies, emotional intelligence, and emotional consonance on followers’ attitudes (emotional engagement and positive emotional reactions) and behaviors (task performance and organizational citizenship behavior). It further scrutinizes the mediating effect of perceived transformational leadership and the moderating effect of perceived emotional sincerity. The target population was leaders and their direct followers in NGOs of Malaysia and Pakistan. Survey questionnaire method was employed, and data were collected from 374 and 383 dyads (leader-follower) respectively by using cluster sampling. PLS-SEM was used for statistical analysis. Findings revealed that leaders’ emotions management played a significant role in shaping followers’ attitudes and behaviors that lead towards leadership effectiveness in NGOs. Leaders’ emotional labor strategies, emotional intelligence, and emotional consonance were related to perceived transformational leadership as well as followers’ attitudes and behaviors. Furthermore, perceived transformational leadership significantly mediated the relationship of leaders’ emotional labor strategies, emotional intelligence, and emotional consonance with followers’ attitudes and behaviors in both countries. Moreover, perceived emotional sincerity moderated the relationship of leaders’ emotional labor strategies with followers’ attitudes and behaviors in both Pakistani and Malaysian NGOs. Few relationships were found to be insignificant in both countries due to contextual factors and particular research settings. Multi-group comparison was also carried out in the study which signified that few relationships were significantly different due to cultural differences. This study enriches the body of knowledge by integrating leaders’ emotions with followers’ attitudes and behaviors. It also provides guidelines to NGOs regarding the management of their leaders’ emotions effectively.